Manajemen Risiko pada Perbankan Syariah - Firdaus, Hafiz Hasbi (Maliki Interdisciplinary Journal, 2025)
Risk management is becoming an increasingly important topic in the financial industry, especially in the context of financial institutions such as Islamic and conventional banks. This article reviews the importance of risk management in two main contexts: Islamic banking and the financial industry in general. Islamic banks have unique characteristics that influence the level of risk they face, including the profit sharing approach in their banking activities. On the other hand, the financial industry as a whole has realized the importance of risk management in maintaining business stability and sustainability. One of the main risks that the financial sector must face is operational risk, which involves various factors such as internal errors, technical failures and procedural violations. This article also discusses market risk, credit risk, and liquidity risk in the context of bank risk management.